Tecnologia digital da informação e comunicação (TDIC) e sua contribuição para o ensino na educação infantil - Santos, Maísa Rodrigues dos (Universidade Federal do Tocantins, 2020)
The present work aimed to discuss the use of information and communication technologies (TDIC) in early childhood education. Nowadays it is possible to notice a great advance in information and communication technologies and this advance has led young children to have contact with the virtual world through games and other technological means at an earlier age. Thus, we sought to understand how the schools that offer early childhood education have used these technologies in order to contribute to the process of teaching and learning of children. In order to reach the proposed objective, a qualitative research was chosen and open questionnaires were used as a data collection tool. To raise the necessary contribution to follow up the proposed discussion sought in the theorists who address the subject the necessary information. The main theorists researched were Kenski (2003), Moran (2011), Sancho (2001), Santos (2014), among others. This research was conducted in a day care center in the city of Arraias-TO. The researched subjects were part of the faculty of that institution. After the conclusion of the research, the results achieved led the author to understand that TDICs play an important role in the process of teaching and learning of children, however education in Brazil has not been able to use it in order to reach its full potential.